Quantitative analysis of 3-monochloropropane-1, 2-diol (3-MCPD) in soy sauce by chromatographic techniques - Nittaya Sudsiri (Prince of Songkla University, 2020)
Thesis (M.S., Analytical Chemistry)--Prince of Songkla University, 2004